Karakteristik Fisikokimia Tepung Talas Beragam Varietas Asal Jawa Barat dan Potensi Aplikasinya - Laeli Dyah Tantri Cahyaningrum; Tjahja Muhandri; Dase Hunaefi; Vallerina Armetha; Ahmad Fadli Alghifari; Edi Santosa (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2026)
Taro (Colocasia esculenta, Xanthosoma sagittifolium, and Xanthosoma undipes) is a food crop with substantial genetic and morphological diversity, offering considerable potential for applications in the food industry. This study aimed to characterize the physicochemical properties of flours produced from 13 taro varieties cultivated in West Java, Indonesia, and to evaluate their potential uses in food processing. Comprehensive analyses were conducted, including proximate composition, functional properties, and pasting profile assessments. The results revealed significant variation among the varieties in both chemical composition and physical charac-teristics. The Belitung variety exhibited the highest amylose content (23.00%), the highest peak viscosity (5029 cP), and the lowest initial pasting temperature (81.35 °C), indicating strong potential for diverse food processing applications. The S28 variety had the highest protein content (11.50%) and the lowest oxalic acid level (1.07%), while the Beneng variety demonstrated the highest dietary fiber content (19.10%) and water absorption capacity (4.26 mL/g). The Pratama 3 variety yielded the highest flour output (29.67%). All varieties were deemed safe for consumption, with hydrogen cyanide (HCN) levels below 3 ppm. These findings highlight the considerable diversity among taro varieties and underscore their potential as alternative raw materials for developing a wide range of food products.